Comparison of Different Signal Peptides for the Efficient Secretion of the Sweet-Tasting Plant Protein Brazzein in Pichia pastoris - Fabrice Neiers; Christine Belloir; Nicolas Poirier; Christian Naumer; Michael Krohn; Loïc Briand (Life, 2021)
Brazzein is a small sweet-tasting protein found in the red berries of a West African evergreen shrub, Pentadiplandra brazzeana Baillon. Brazzein is highly soluble and stable over a large pH range and at high temperatures, which are characteristics that suggest its use as a natural sweetener. However, Pentadiplandra brazzeana culture is difficult at a large scale, limiting the natural source of brazzein. Heterologous expression of brazzein has been established in numerous systems, including bacteria, yeast, and transgenic plants. Brazzein requires four disulfide bonds to be active in eliciting an intense sweet taste, and the yeast Pichia pastoris appears to be one of the best options for obtaining functional brazzein in high quantities. Employing yeast secretion in the culture medium allows us to obtain fully active brazzein and facilitate purification later. To increase yeast secretion, we compared seven different signal peptides to successfully achieve brazzein secretion using the yeast P. pastoris. The brazzein proteins corresponding to these signal peptides elicited activation of the sweet taste receptor functionally expressed in a cellular assay. Among these tested signal peptides, three resulted in the secretion of brazzein at high levels.